Diminution in energy expenditure during lactation. Issue 6518 (15th February 1986) - Illingworth, P J; Jung, R T; Howie, P W; Leslie, P; Isles, T E
Abstract : Energy expenditure at rest and in response to a meal and to an infusion of noradrenaline was measured in 12 lactating women and compared with that in seven bottle feeding women and seven non-pregnant, non-lactating controls. The energy response of the lactating women was remeasured after lactation stopped. During lactation the resting metabolic rate was unaltered but there was a reduced response to infusion of noradrenaline and to a meal, which increased to normal control values after lactation stopped. Such reductions in expenditure were not found in women who had been bottle feeding and were tested at a similar six to eight weeks post partum. These findings suggest that metabolic efficiency is enhanced in lactating women, who may not need to increase energy intake to the extent suggested by current recommended dietary allowances.